2007
DOI: 10.1111/j.1442-2042.2007.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy in children: Results and short‐term complications

Abstract: Aim:The introduction of extracorporeal shock wave lithotripsy represented an important evolution in urinary tract lithiasis management. The aim of this study is to describe the results of extracorporeal shock wave lithotripsy for the treatment of urinary tract lithiasis in children, focusing on the index of elimination of the calculi and the complications occurring during the procedure and during the following three months. Methods: From September 1991 to July 2002, 135 children between one and 12 years, suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
13
0
4
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] The majority of these studies used the stone-free rate as the main indicator for treatment success. [3][4][5][6][7] Despite the fact that stonefree status is the ultimate goal of any stone treatment modality, it is important also to measure the Efficacy Quotient (EQ), because it also takes into consideration factors that increase patient's morbidity and anxiousness and result in waste of patient time and hospital resources such as the retreatment rate and the rate of auxiliary procedures. Despite this, only very few studies have reported on the EQ as an important indicator of treatment success in the upper tract urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] The majority of these studies used the stone-free rate as the main indicator for treatment success. [3][4][5][6][7] Despite the fact that stonefree status is the ultimate goal of any stone treatment modality, it is important also to measure the Efficacy Quotient (EQ), because it also takes into consideration factors that increase patient's morbidity and anxiousness and result in waste of patient time and hospital resources such as the retreatment rate and the rate of auxiliary procedures. Despite this, only very few studies have reported on the EQ as an important indicator of treatment success in the upper tract urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with what is reported in literatures. [11,22] In this study there was a significant relation between the size of stone and the development of pain after SWL (P = .003), with larger stones causing more degree of pain after SWL. This finding is supported by Sun et al, and Tiselius et al [10,19] Increasing the energy level did not cause increased risk of developing post SWL pain (P = .65).…”
Section: Discussionmentioning
confidence: 52%
“…Se ha comunicado en la bibliografía la ausencia de cálculos en el 75 al 92% de los pacientes después de uno a tres tratamientos de LEOC 10,[14][15][16][17][18][19] .…”
Section: Comentariounclassified
“…Todas ellas eran leves y pasajeras, e incluían hematuria, "calle litiásica", obstrucción ureteral e infección urinaria con o sin fiebre 10,15,20 .…”
Section: Comentariounclassified